Anthropology of Buddhism and Hinduism: Weberian Themes - Gellner, David N (New Delhi, 2001)
Max Weber's ideas have had enormous influence in theoretical sociology. But what he wrote about Asia has more often been cited by specialists to illustrate his errors rather than to derive inspiration. This collection of essays both engages with Max Weber's work, and attempts to use his general approach, combined with detailed ethnography from Nepal and Japan, to attack critical questions in the anthropology and sociology of Buddhism and Hinduism. These range from the relationship of Buddhist religious specialists (monks and priests) to shamanic practitioners, to the way in which Brahmanical ideals have spread through history and are expressed in a traditional Hindu city, to the question of how to frame sociological comparisons between similar religious systems in different cultures.
Keywords: Hinduism